Dental status and prosthetic rehabilitation in elderly population in relation to socioeconomic factors in Republika Srpska - Radović Igor; Davidović Lado; Krunić Jelena; Stojanović Nikola (Serbian Medical Society - Dental Section, Belgrade, 2015)
The aim of this study was to determine dental status and prosthetic rehabilitation in elderly population in relation to socioeconomic factors in Republika Srpska. Material and Methods The study included 262 subjects (133 males and 129 females) aged 65-74 years. Dental status was assessed using DMFT index and its components (D - decayed, M - extracted, F - filled tooth) and analysed in relation to socioeconomic factors: gender, level of education and monthly income. Prosthetic restorations were recorded for both jaws in accordance with criteria of the World Health Organisation. Results The mean DMFT was 27.2. Females had the highest DMFT index score (29.1) while highly educated subjects had the lowest score (22.7). The mean number of missing teeth was 22.7. There were 28.2% edentulous respondents. Significant difference in the number of edentulous persons was recorded in relation to gender, education and monthly income. In total, 16.8% of subjects had functional dentition (≥20 natural teeth). 48.5% and 32.1% of elderly respondents were found to have at least one form of prosthetic restoration in upper and lower jaw, respectively. Complete dentures were the most common prosthetic restorations. Conclusion Socioeconomic factors influenced dental status in elderly population. Removable dentures were more common restorations compared to crowns and bridges.